Regulating sperm donation for non-Muslim in Malaysia / Nur Medina Hidayah Muazam Shah ... [et al.] - Muazam Shah, Nur Medina Hidayah; Ismadi, Ermadieyani; Ishak, Noor Dayang Saleha; Jaafar, Fathi Nasyrah (2013)
This research project is introducing the need for Malaysia to regulate one of the Assisted Reproduction Technology (ART) that had been used in several fertility practice; the sperm donation. Although the scale of this method of ART was not yet widely used, the rights of the parties involved were not given a proper safeguard. There are a lot of problem that can arise out of the lack of regulation that observed the sperm donation procedure, but, we chose to address three main problems. The problems are the ambiguity of the rights between the donor, the donee and the conceived child, the lack of proper procedure and also the uniformity of law that was adopted by different fertility practice. Through out this research, we tried to compare the law that was used in countries that already acknowledge the need for proper legislation to regulate sperm donation activity. However, this research put a focus more on the law that was used in the United Kingdom. We make an effort to make the reader and also future researchers to understand our fears out of unregulated sperm donation procedure by providing a comparison study based on the problem statement and also the recommendation that we deduct after the research was done. We found that it is necessary to provide legal safeguard for the person that involved in this procedure.